Comparative Characteristics of Future Technical Specialists Training Educational Programs in Germany and Ukraine - Dynovych, Anna (Journal of Vasyl Stefanyk Precarpathian National University, 2025)
Educational programs are an integral part of the higher education institutions functioning. An educational program is a system of relevant educational components determined at the highest level for the optimal possession of a certain qualification. The educational program specifies the requirements, disciplines, credit numbers, diploma projects, and practical classes necessary for completion. The scope of educational programs differs for each higher education level and corresponding focus. The article examines various technical specialties and educational programs of higher education institutions in Germany and Ukraine. The key disciplines are analyzed, and the corresponding credits number students must complete to successfully obtain a diploma are indicated. Certain differences in the forms of control and the number of tasks required for learning are indicated. The existing competencies list of an education seeker with the normative content of the education seeker's training is highlighted, where deadlines and study results are displayed. The research includes the current trends analysis of the technical education development in Germany and Ukraine. A brief introduction to the latest technologies and teaching methods is presented. An important aspect is the comparison of the requirements for students' practical training and the possibility of internships at enterprises. The issue of students’ academic mobility and the exchange studies possibility is shown. The article examines some educational programs of the Technical University of Munich and Zhytomyr Polytechnic State University. The programs “Management and Technologies”, “Electrical Engineering and Information Technologies”, “Computer Science”, and “Software Engineering” are analyzed. The necessary documents for a higher technical specialty admission are indicated. The importance of interdisciplinary connections for the students’ better development is emphasized.